SENSOR SUHU BERBASIS BAHAN FERROELEKTRIK FILM Ba0,55 Sr0,45TiO3 (BST) BERBANTUKAN MIKROKONTROLER ATMEGA 8535 - Ridwan Siskandar (Jurnal Biofisika, 2013)
Growth of pure Ba0.55Sr0.45TiO3 (BST) film on p-type silicon (100) substrates with two treatments on the enhancement and depletion (pretreatment of the substrate which is heated up to first at a temperature of 800°C for 15 hours before the spilled solution BST) with the method Chemical solution Deposition (CSD) and spin coating at 3000 rpm rotational speed for 30 seconds. Films (both on the type of enha ncement treatment and type of deples treatment) in put on top of the substrate is then heated at a temperature of 800oC, 850oC and 900oC for 15 hours . Of BST film obtained was then carried out the characterization of the value range, sensitivity, resolution BST films, the level of accuracy and hysteresis. Results showed that 850 oC enhancement BST film is the best film that can be used as a temperature sensor to read the changes in the environment (temperature only) ATMega8535 based microcontroller. Output (voltage generated) amplified by differential amplifier circuit and non-inverting amplifier. Subsequently processed into digital data output on the Analog Digital Converter (ADC) internalATMega8535. Digital data is processed by the microcontroller. Visualization using measuring 16x2 Liquid Crystal Display (LCD) display which can change the voltagein units of degrees celsius ( oC) when given a BST film temperature stimuli